Nanomaterials for sustainable hydrogen production by (photo)electrolysis - Zhang, Liping (2018)
Global energy and environmental crisis have received enormous research attention for a long time. Fossil fuels as the primary energy source, comprised 86% of global energy consumption in 2015. However, the consumption of this nonrenewable resources brings about not only the environmental problem such as global warming, but also the economic problem since fossil fuels’ price increased rapidly due to the limited recoverable reserves. With the inexhaustible irradiation from the Sun, solar energy is agreed to be the most promising renewable energy resource. Inspired by Mother Nature, converting solar energy to chemical energy has been intensively studied. Systems including photocatalytic and photoelectrochemical water splitting have been developed to fulfill the ultimate goal of high efficient solar-to-hydrogen conversion. The overall objective of this interdisciplinary research program is to improving the overall solar-to-hydrogen efficiency by rational design of catalytic nanomaterials. Firstly, a new kind of photosensitizer were studied for improved light harvesting. A series of MOFs based on MIL-125 have been demonstrated as promising photosensitizers for PEC water oxidation. When applied MOFs/TiO2 heterostructure materials as the photoanodes for solar water oxidation, the photocurrent of TiO2 could be improved by nearly 100% under visible light through sensitization with aminated Ti-based MOFs. Incident photon-to-current conversion efficiency matches well with the UV–vis absorption of modified TiO2 photoanodes, which confirm the sensitization of MOF materials. Highly porous structure of MOFs enables further tuning of light harvesting efficiency. By coupling with plasmonic Au nanoparticles, the light absorption could be further improved due to the LSPR effect. Secondly, a new noble-metal free HER catalyst were synthesized for improved reaction kinetics. A general one step method to prepare ultra-small transition-metal carbide nanoclusters encapsulated in N, S co-doped graphene were developed, and used for all pH hydrogen evolution reaction. The as-prepared MoC1-x/C materials possess ultra-small particle size (2.8 nm) with narrow size distribution (1.8 to 3.2 nm), which provides lots of catalytically active sites. The intimate interaction between transition-metal carbide nanoclusters and N, S co-doped graphene modifies the binding strength of protons on transition-metal carbides. The porous graphene supports enable quick charge transport and fast reactant/product diffusion. All of which contribute simultaneously, giving rise to the excellent HER performance of the transition-metal carbide/graphene composite catalysts. Finally, photoelectrochemical reforming of biomass-derived alcohol oxidation has been developed for decreased overall energy consumption in solar-to-hydrogen system. In this new system, pure hydrogen and value-added chemicals were simultaneously produced driven by solar energy at room temperature. The hydrogen quantum efficiencies reach 80% across the entire visible region of the solar spectrum, leading to an ultrahigh hydrogen production rate of 7.91 μmol min-1 cm-2 illumination area of a single-junction GaAs solar cell under AM 1.5G illumination. Moreover, by properly choosing the anodic catalyst, alcohols can be selectively converted to useful liquid chemicals with nearly 100% selectivity.